1999
DOI: 10.1007/s001220051265
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of QTL for downy mildew resistance in maize

Abstract: Quantitative trait loci (QTLs) of maize involved in mediating resistance to Peronosclerospora sorghi, the causative agent of sorghum downy mildew (SDM), were detected in a population of recombinant inbred lines (RILs) derived from the Zea mays L. cross between resistant (G62) and susceptible (G58) inbred lines. Field tests of 94 RILs were conducted over two growing seasons using artificial inoculation. Heritability of the disease reaction was high (around 70%). The mapping population of the RILs was also score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…The mapping of quantitative trait loci (QTLs) make feasible the detection, localization and characterization of genetic factors contributing to the variation of polygenically inherited traits (reviewed by Young 1996). In maize, QTLs that contribute towards variation in disease resistance against sorghum downy mildew (Agrama et al 1999), gray leaf spot (Bubeck et al 1993;Saghai-Maroof et al 1996), northern corn leaf blight (Dingerdissen et al 1996;Freymark et al 1993) and stalk and ear rot (Pe et al 1993;Perez-Brito et al 2001) have been identified.…”
Section: Introductionmentioning
confidence: 98%
“…The mapping of quantitative trait loci (QTLs) make feasible the detection, localization and characterization of genetic factors contributing to the variation of polygenically inherited traits (reviewed by Young 1996). In maize, QTLs that contribute towards variation in disease resistance against sorghum downy mildew (Agrama et al 1999), gray leaf spot (Bubeck et al 1993;Saghai-Maroof et al 1996), northern corn leaf blight (Dingerdissen et al 1996;Freymark et al 1993) and stalk and ear rot (Pe et al 1993;Perez-Brito et al 2001) have been identified.…”
Section: Introductionmentioning
confidence: 98%
“…The inbred parent GBIK was highly resistant, and an inbred Redlan was highly susceptible. The RI populations have several advantages for use in mapping QTLs, which have been described by several authors (Knapp and Bridges 1990;Burr and Burr 1991;Austin and Lee 1996;Agrama et al 1999). …”
Section: Discussionmentioning
confidence: 99%
“…The program MAPMAKER/EXP 3.0 (Lander et al 1987) was used to establish the linkage map using the Kosambi function. Mapping of QTLs was performed using the single-factor analysis as described by Tuinstra et al (1997) and Agrama et al (1999). The PROC GLM procedure in SAS was used to detect significant associations between segregating markers and the resistance, as a quantitative trait.…”
Section: Methodsmentioning
confidence: 99%
“…However when several resistance genes are initially present in a donor parent, some of them may be lost during the breeding programs. The chance of losing resistance genes can be reduced if they are detected early (Agrama et al, 1999). The mapping of quantitative trait loci (QTLs) makes feasible the detection, location and characterization of genetic factors contributing to the variation of polygenically inherited traits (Young, 1996).…”
Section: Molecular Marker Analysis For Resistance To Sorghum Downy MImentioning
confidence: 99%
“…The QTL mapping analysis for SDM resistance in Egyptian maize germplasm (Agrama et al, 1999) using single-factor analysis revealed three QTLs on two chromosomes (Chromosome 1 and 9) cumulatively explaining 53.6 per cent of the phenotypic variance. All three QTLs were contributed by the resistant parent G62 and have an additive gene action.…”
Section: Molecular Marker Analysis For Resistance To Sorghum Downy MImentioning
confidence: 99%